The 17th International Congress of Myriapodology - Panha, Somsak (Tropical Natural History, 2017)
The International Congress of Myriapodology (ICM) aims at the interpretation of scientific knowledge about Myriapoda and Onychophora, which include diplopods, pauropods, symphylans, chilopods and onychophorans. Participants are not limited to experts and specialists but also include researchers from other relevant fields as well as amateurs from several communities who are interested in these spectacular animals. Diverse topics of presentation and discussion are encouraged, exploring the latest findings on myriapods and onychophorans at both global and regional scales. The goal is to build on research connections across the scientific community that has been forged since the first ICM in Paris in 1968. Up to date, the previous congresses have been regularly attended by participants from more than 30 countries around the world.